2017
DOI: 10.1038/bjc.2017.120
|View full text |Cite
|
Sign up to set email alerts
|

Pre-diagnosis diet and survival after a diagnosis of ovarian cancer

Abstract: Background:The relationship between diet and survival after ovarian cancer diagnosis is unclear as a result of a limited number of studies and inconsistent findings.Methods:We examined the association between pre-diagnostic diet and overall survival in a population-based cohort (n=811) of Australian women diagnosed with invasive epithelial ovarian cancer between 2002 and 2005. Diet was measured by validated food frequency questionnaire. Deaths were ascertained up to 31 August 2014 via medical record review and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 61 publications
5
50
5
1
Order By: Relevance
“…Regarding vegetable subgroups, no association between cruciferous vegetable consumption and overall mortality was detected ( Supplemental Figure 1 ). Null results were also found for the intake of other vegetable or fruit subgroups (e.g., green leafy, and yellow and red vegetables, and citrus fruit) ( 59 62 ).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Regarding vegetable subgroups, no association between cruciferous vegetable consumption and overall mortality was detected ( Supplemental Figure 1 ). Null results were also found for the intake of other vegetable or fruit subgroups (e.g., green leafy, and yellow and red vegetables, and citrus fruit) ( 59 62 ).…”
Section: Resultsmentioning
confidence: 87%
“…The 4 meta-analyzed studies on ovarian cancer patients ( 59 62 ) showed an inverse association between total vegetable and total fruit intake before diagnosis and overall mortality (HR: 0.78; 95% CI: 0.66, 0.91 and HR: 0.82; 95% CI: 0.70, 0.96, respectively) ( Figure 3 A and B ). Although the results are significant, the prediction interval of both meta-analyses will be expected to be outside the protective HR range in 95% of all the population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 Pre-diagnosis food intake also affected the prognosis of invasive ovarian cancer patients: high consumption of green leafy vegetables was correlated with a 30% reduced risk of death, high consumption of fish was associated with a 26% reduced risk of death, high intake of fibre was associated with a 31% reduced risk of death, but a high glycaemic index was associated with an increased risk of death (HR 1.28: 95% CI 1.01, 1.65). 15 However, the dietary effects on ESCC survival has been less well reported. ESCC is the main pathological type of EC in China and the composition of the Chinese diet is different compared with Western diets.…”
Section: Discussionmentioning
confidence: 99%
“…One study suggested women who were inactive before diagnosis had particularly poor survival if they were also current or former smokers (109). Some studies have also reported poorer survival associated with certain features of diet (110)(111)(112), and with lower serum 25hydroxyvitamin D levels (113). At least some of these associations relate to pre-diagnosis exposure, which is obviously not retrospectively modifiable by the patient.…”
Section: Potentially Modifiable Exposuresmentioning
confidence: 99%